Hygienic-sanitary profile of an artisanal ice cream establishment located in Juazeiro, BA (Research, Society and Development, 2021)
The industry and the artisanal production of edible ice-cream products is a segment very appreciated by a large part of the population, being very attractive especially for children. This is a descriptive, cross-sectional, qualitative and quantitative study. The hygienic-sanitary evaluations were carried out by applying the checklist according to RDC No. 216/2004, ANVISA, and the microbiological analysis for the counting of Staphylococcus aureus and Total Coliforms, where water samples were collected from the bags, from the blender cup and a basin. Regarding good handling practices, this micro company was classified as Group 2 (57% adequacy). The microbiological analysis indicated the presence of S. aureus in passion fruit bags, but they are tolerable to the legislation. The blender cup showed total coliforms (2.2 x 10³ CFU/cm²), where this count should not exceed the threshold of < 100 CFU/cm² on surfaces. The need for a professional such as a nutritionist is evident in order to meet all the necessary demands, from food preparation to transport, which would avoid food contamination.